Electrocardiographic changes in the acute hyperkalaemia produced by intragastric KCl load in rats - Fazan, Frederico [UNESP]; Colombari, Debora Simoes de Almeida [UNESP]; Menani, Jose Vanderlei [UNESP]; Fazan, Rubens; Colombari, Eduardo [UNESP] (Wiley-Blackwell, 2021)
New Findings What is the central question of this study? This study presents a new model for studying the rapid onset of severe, acute hyperkalaemia in rats with intact kidney function by administering an intragastric KCl load. What is the main finding and its importance? This new model of intragastric KCl load produces a reliable and reproducible model for studying the rapid onset of severe, acute hyperkalaemia in rats with intact kidney function. We report unprecedented rapid changes (30 min) in ECG, blood pressure and various arterial blood analyses with this new model, providing a solid foundation for future experiments in this field. A variety of animal models have been proposed to study hyperkalaemia, but most of them have meaningful limitations when the goal is to study the effect of potassium overload on healthy kidneys. In this study, we aimed to introduce a new approach for induction of hyperkalaemia in a reliable and reproducible animal model. We used intragastric administration of potassium chloride [KCl 2.3 M, 10 ml/(kg body weight)] to male Holtzman rats (300-350 g) to induce hyperkalaemia. The results showed that this potassium load can temporarily overwhelm the renal and extrarenal handling of this ion, causing an acute and severe hyperkalaemia that can be useful to study the effect of potassium imbalance in a variety of scenarios. Severe hyperkalaemia (>8 meqiv/l) and very profound ECG alterations, characterized by lengthening waves and intervals, were seen as early as 30 min after intragastric administration of KCl in rats. In addition, a transient increase in arterial blood pressure and time-dependent bradycardia were also seen after the KCl administration. No metabolic acidosis was present in the animals, and the potassium ion did not increase proportionally to chloride ion in the blood, leading to an increased anion gap. In conclusion, the results suggest that intragastric KCl loading is a reliable model to promote rapid and severe hyperkalaemia that can be used for further research on this topic.
Keywords: arterial blood gas; electrocardiogram; hyperkalaemia; potassium